Women Empowerment in Health: Systematic Review - Rumpiati Rumpiati; Bhisma Murti; Yuly Peristiowati; Katmini Katmini (Indonesian Journal of Medicine, 2023)
Background: Women's Empowerment is an integral part of human rights and development because the value system leads to the development of a good family, community, and country. Empowerment of women can have important implications for health in the form of education, access, and change in terms of services and family welfare. This systematic review aims to determine the influence and model of empowerment of women in the health sector.Subjects and Method:  This systematic review begins with searching data using 5 databases with keywords women’s empowerment, women’s health, and empowerment model. Researchers used five databases, PubMed, Scopus, Science Direct, Springer Link, and BMC with a range of 2017-2022. Articles were searched using keywords that had been determined by the researcher then the articles were extracted based on criteria inclusion and exclusion using the PRISMA protocol. Thus, 11 articles were found that matched the criteria of JBI's critical assessment tool for analysis.Results:  A total of 11 studies were included in the analysis originating from several countries such as Iran, Australia, and the Netherlands. Empowerment of women is a multilevel construction that refers to individuals, organizations, and society. Women's empowerment needs to involve mutual respect, critical reflection, caring and group participation, where people gain greater access to and control over their resources.Conclusion:  Factors that influence women's empowerment are age, education, occupation, religion, marital status, socio-economic, demographics, different behavior, special characteristics of society, household harmony, place of residence, mobility, decision-making, social life, media exposure, information technology, socio-culture and access to health services. The women's empowerment model that has been developed refers to 3 domains: micro, meso, and social capital levels; as well as macro level.Keywords: empowerment, women, model, healthCorrespondence: Rumpiati. Institute of Health Science STRADA Indonesia Jl. Sumberece 37 Tosaren Pesantren Kota Kediri. Email: rumpiati75@gmail.com. Mobile: +62812-3007-1403.Indonesian Journal of Medicine (2023), 08(02): 194-203https://doi.org/10.26911/theijmed.2023.08.02.09